Review of geochemical processes in CCUS : Mechanisms, processes, and implications - Lu, Shuaiyi; Jiang, Pan; Cong, Lianghan; Zheng, Tianqi; Hao, Yankai; Lü, Xiaoshu (Elsevier, 2025)
The emission of greenhouse gases has resulted in the deterioration of the global climate, leading nations worldwide to adopt measures to mitigate the environmental impact of carbon emissions. Carbon dioxide capture, utilization and storage (CCUS) is an emerging large-scale greenhouse gas emission reduction technology with the potential to become an important means of mitigating the greenhouse effect in the future. However, the geochemical reactions accompanying CCUS implementation critically impact system stability and the environment. This review systematically examines the geochemical reaction mechanisms in CCUS reservoirs, including clastic rock, claystone, carbonate rock, igneous rock, and coal, and their effects and risks on CO2 sequestration systems. It has been demonstrated that geochemical reactions are prevalent in various types of CCUS, including mineral dissolution, CO2 mineralization, and adsorption of CO2 by rocks. These reactions may alter rock strength, caprock sealing integrity, fracture development, and groundwater ion concentrations, influencing sequestration outcomes. The study highlights challenges in CCUS geochemical research and proposes future directions. By enhancing understanding of reaction processes and risks, this work provides insights for CCUS operation, monitoring, and research.
Keywords: CCUS; Geochemical processes; CO2 injection; Geochemical risks; Sequestration efficiency; fi=Energiatekniikka|en=Energy Technology|